Power transmission system midpoint voltage fixation using SVC with genetic tuned simple PID controller - Azeez Joodi, Mohanad; Kasim Ibraheem, Ibraheem; Mohammed Tuaimah, Firas (International Journal of Engineering and Technology, 2019)
Contingency in power system is widely used to predict the effect of outages in power systems, like failures of equipment, transmission line, etc. The transmission system voltage will be affected due to these contingencies. To stabilize its voltage, especially the midpoint voltage, the Static VAR Compensator (SVC) is one of the shunt connected devices, which can be utilized for voltage fixation in power systems. The dynamic equations for the Single-Machine-Infinite-Bus (SMIB) SVC model will be presented which is expressed in terms of linearized state-space equations. Then, with the aid of MATLAB, the plant of the system model will be given under various loading conditions, and four suggested scenarios have been proposed as contingencies in the power transmission system. The SVC will be controlled using a simple PID controller tuned through the Genetic algorithm, the results were promising, and the midpoint voltage step response has been enhanced.Â Â